Pulmonary function, respiratory muscle strength, and core strength: A comparative study of Paralympic and Olympic athletes - Akinoglu, B.; Ünüvar, E.; Shehu, S. U.; Kocahan, T.; Rosemann, T.; Weiss, K.; Knechtle, B. (Sports Medicine and Health Science, 2025)
Purpose The significance of pulmonary function, respiratory muscles, and core muscle strength in athletes is extensively studied, however the correlation between these variables remains unexplored in athletes with disabilities. This study examines the relationship between these parameters, aiming to identify potential disparities relative to athleticism and disabilities.